2019
DOI: 10.3390/mi11010023
|View full text |Cite
|
Sign up to set email alerts
|

Nanoantenna Structure with Mid-Infrared Plasmonic Niobium-Doped Titanium Oxide

Abstract: Among conductive oxide materials, niobium doped titanium dioxide has recently emerged as a stimulating and promising contestant for numerous applications. With carrier concentration tunability, high thermal stability, mechanical and environmental robustness, this is a material-of-choice for infrared plasmonics, which can substitute indium tin oxide (ITO). In this report, to illustrate great advantages of this material, we describe successful fabrication and characterization of niobium doped titanium oxide nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It is worth noting that the proposed process is generic and might be very efficient for the production of nanostructures of a wide variety of alternative nonmetallic conductors, which are usually grown by sputter deposition, such as molybdenum nitride (MoN), tantalum nitride (TaN), ,, niobium nitride (NbN), In-doped tin oxide (ITO), ,, aluminum- or gallium-doped zinc oxide (AZO, GZO), ,,, niobium-doped titanium oxide (NTO), partly reduced molybdenum oxides MoO x ( x < 3), , and vanadium dioxide (VO 2 ), which exhibits a metal–insulator transition. , All these conductors have been proposed as alternative plasmonic materials, whose plasmonic activity spans the far-ultraviolet to medium-infrared range. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the proposed process is generic and might be very efficient for the production of nanostructures of a wide variety of alternative nonmetallic conductors, which are usually grown by sputter deposition, such as molybdenum nitride (MoN), tantalum nitride (TaN), ,, niobium nitride (NbN), In-doped tin oxide (ITO), ,, aluminum- or gallium-doped zinc oxide (AZO, GZO), ,,, niobium-doped titanium oxide (NTO), partly reduced molybdenum oxides MoO x ( x < 3), , and vanadium dioxide (VO 2 ), which exhibits a metal–insulator transition. , All these conductors have been proposed as alternative plasmonic materials, whose plasmonic activity spans the far-ultraviolet to medium-infrared range. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
“…The operating principle is the same as that of the Seebeck effect, wherein we excite the nanoantenna designs with various laser wavelengths (650 nm, 940 nm, and 1550 nm) that detect voltages produced by the properties of intersecting materials. Compared to the state of the art, to our knowledge, this is the first time that peak percentage voltage hike detection is attained when utilizing infrared energy [26][27][28][29].…”
Section: Introductionmentioning
confidence: 97%
“…Ngo et al reported the synthesis and demonstration of niobium-doped titanium dioxide for the application in plasmonic antenna and surface-enhanced infrared absorption [ 6 ]. The nanopatterns prepared by electron beam lithography, plasma etching/ashing processes showed well-defined antenna resonance as well as clear polarization/size dependence, which confirms that these materials are suitable for infrared plasmonic applications.…”
mentioning
confidence: 99%